Eksplorasi Budaya dalam Konseling: Kajian Nilai-nilai Pada Suku Melayu Jambi - Pramudita, Galuh; Muslihati, Muslihati (JKI (Jurnal Konseling Indonesia), 2024)
: Indonesia has a wealth of culture contained in customs and traditions in each region. One of the regions in Indonesia that contains a diversity of customs and cultural traditions is Jambi. Jambi is a province on the island of Sumatra. Jambi is included in the Malay group. Jambi Malay has various customs and traditions that the local community has preserved from generation to generation. The values ​​contained therein are implemented in everyday life as a benchmark for what is allowed, not allowed, and even what must be done in community life. This study aims to explore the values ​​of the Jambi Malay tribe that can be applied and implemented in multicultural counseling. The method used in this study is a systematic literature review to find and explore cultural values ​​in the Jambi Malay tribe that can be used in the counseling service process. This study follows three stages of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) flowchart, namely identification of the records, screening for possible and eligibility, and inclusion of the studies. The results of this study are the discovery of several cultural values ​​taken from several traditions in Jambi that can be applied in the counseling process